2013
DOI: 10.1136/heartjnl-2013-303950
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine does not increase the risk of atrial fibrillation: a systematic review and meta-analysis of observational studies

Abstract: Caffeine exposure is not associated with increased AF risk. Low-dose caffeine may have a protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 50 publications
2
46
0
2
Order By: Relevance
“…We speculated another component of green tea might reduce the effect of EGCG. Green tea contains large quantities of caffeine which is not directly associated with decreased incidence of AF [13, 49- 50]. High frequency-high concentration, or long-term green tea consumption may lead to high cumulative doses of caffeine which might contribute to an incidence of AF [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated another component of green tea might reduce the effect of EGCG. Green tea contains large quantities of caffeine which is not directly associated with decreased incidence of AF [13, 49- 50]. High frequency-high concentration, or long-term green tea consumption may lead to high cumulative doses of caffeine which might contribute to an incidence of AF [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of sympathetic activity have been shown to be detrimental [51, 55]. Thus, while caffeine intake might be associated with increased incidence of AF, data remains inconclusive at this point in time [49]. Persistent AF risk for patients decreased with the increasing frequency, duration and concentration of green tea consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are looking for clear guidance with respect to how best to reduce their risk and burden of AF. Emerging evidence related to diet, 80 caffeine, 150 yoga, 151 and acupuncture 129 represent potentially important steps forward in the incorporation of patient-driven prevention research. Social networking may have a significant role in the prevention and treatment of AF, similar to ongoing efforts in obesity and diabetes management.…”
Section: The Need For Innovative Research Structures and Methodsmentioning
confidence: 99%
“…Caffeine continues to be a dietary compound of public health interest. Recent meta-analyses have examined the association of caffeine intake with diseases and conditions such as breast cancer (3) and atrial fibrillation (4), and associations with positive health outcomes have been observed in some cases, such as with Parkinson’s disease (5). Caffeine consumption is generally considered to be safe; however, fatalities due to apparent caffeine intoxication (6), as well as associations of adverse health events with caffeinated “energy” drinks (7) have been reported.…”
Section: Introductionmentioning
confidence: 99%